Pengaruh Dana Pensiun terhadap Keberlanjutan Fiskal - Alinda Maharani (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2025)
This study investigates the impact of pension fund schemes on fiscal sustainability. The data used is time data for the period 2006 - 2022 using ECM analysis technique. The research found that pension scheme affects fiscal sustainability.